An Experimental Investigation into the Performance of Conventional and Winged Type Subsoilers - Kumar, Arun; Thakur, T C (Journal of Agricultural Engineering, 2007)
An experiment was conducted at Crop Research Centre of G B Pant University of Agriculture and Technology, Pantnagar in Randomized Block Design to compare the performance ofdifferent types of subsoiler viz. conventional curved leg, conventional straight leg, winged straight leg and winged with shallow leading tines on the basis of draft, soil disturbance and specific draft at working depths of 250, 300, 350 and 400 mm. The soil of the experimental field was silty clay loam (Sand 31%, Silt 37%, and Clay 32%). Results have shown the critical depth of conventional curved leg subsoiler at about 350 mm depth of operation. However, the critical depth for other subsoilers was not observed even upto 400 mm depth. At 350 mm working depth, the draft force for winged subsoiler with shallow leading tines increased by 39.75% and 31.81% over conventional curved leg and straight leg subsoilers while the soil disturbance increased by 3.03 (203.25%) and 2.35 (135.42%) times, thereby, reducing the specific draft by 53.90% and 44.00%, respectively.